Son of Virginia : a life in America's political arena - Wilder, Lawrence Douglas, 1931- (LP, 2015)
About the first elected African American governor in American history. This book details the events of the author's life to paint a portrait of the changing face of America. It will be a story of constant struggle and conflict, not only Wilder's struggle, but also that of courageous people who stood up to decades of discrimination, corruption and greed. The book will stand as a road map for continued American progress in our elections and laws and a stark warning of what may happen if we relax our commitment to this program.